How community ecology can improve our understanding of cholera dynamics - CONSTANTIN DE MAGNY, Guillaume; Hasan, Nur A.; Roche, Benjamin (Frontiers in Microbiology, 2014)
Understanding the seasonal emergence and reemergence of cholera is challenging due to the complex dynamics of different protagonists. The abundance of Vibrio cholerae, the causative agent of cholera and a natural inhabitant of aquatic environments, fluctuates according to abiotic and biotic factors. Among the biotic factors, the zooplankton community dynamics has been suggested to play a pivotal role in the survival, persistence and natural competence of V. cholerae. However, factors regulating V. cholerae population structure and seasonal dynamics are still not fully understood. Investigation of the temporal shifts and variability in aquatic community composition in relation to the occurrence or abundance of V. cholerae appears very promising yet remained underexplored. Recent advances in metagenomics, facilitated by high-throughput ultra deep sequencing, have greatly improved our ability for a broader and deeper exploration of microbial communities including an understanding of community structure, function, as well as inter- and intra-specific competitions. Here, we discuss possible areas of research focusing how combination of community ecology and metagenomic approaches could be applied to study the cholera system.